Audit Sertifikasi Iso 9001:2015 Dan Implikasinya di Institut STIAMI - Wiwiet Prihatmadji; Noviandari Sari Utami; Ana Chaerunisyah; Dinda Aulia Rahman; Rangga Dalu Aji Toana (JISAMAR (Journal of Information System, Applied, Management, Accounting and Research), 2022)
The ISO 9001 certification audit process for the STIAMI Institute was carried out on August 24 and 25 2018 by the SGS certification body with findings in the form of twenty (20) classifications of non-conformance finding clauses, and forty-three (43) cases of observation findings. The implications of the findings of the certification audit are in the form of five (5) main steps for improving the quality management system at the STIAMI Institute, namely: (1) Institutional Leaders (Rector) make orders to each Head of Division and Head of Study Program to monitor, measure, achieve of Quality Goals, take corrective steps towards targets that have not been achieved (against the targets and Action Plans that have not been achieved), and prevent the failed targets/processes from being evaluated again. Records, and targets for completion, prepares the dating of Documents and Records, control of Documents and Records of validation and verification records. Each Section provide up date the Master List of Documents and Records both Hard and Soft Copy, (3) Socialization of Quality Policy as an Institution's commitment to quality, programmed systematically in every meeting both in general and in general at Serial Friday Events, Meetings by Field or Study Programs, and Leadership Meetings so that the Quality Policy is understood by all employees, including the Quality Assurance System, ISO 9001 Quality Manual, ISO 9001 Quality Procedures, and internal regulations in each respective field, (4) Carrying out ISO 9001:2015 internal quality audits with an audit topic according to the quality audit requirements of ISO 19011:2018, and (5) Management Review Meeting scheduled in the Leadership Meeting with a meeting agenda as required by ISO 9001.